Comparison of Malaysian and Indonesian Whistleblower Legal Protection as a Tool for Criminalization Elimination - Hosnah, Asmak ul; Ghapa, Norhasliza binti; Nuraeny, Henny; Djarkasih Putro, Sapto Handoyo; Prihatini, Lilik (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Whistleblowers in Indonesia face significant risks due to insufficient legal protection, particularly in cases involving corruption. The absence of comprehensive safeguards often leads to retaliation and even criminalization. This study aims to examine and compare the legal frameworks governing whistleblower protection in Indonesia and Malaysia, with the goal of proposing decriminalization strategies for whistleblowers in Indonesia. Employing a normative juridical approach and comparative legal analysis, this research draws on relevant statutes and case studies from both countries. The results show that Malaysia, through its Whistleblower Protection Act 2010, provides more robust protection mechanisms, including confidentiality guarantees, standardized reporting procedures, legal immunity for disclosures made in good faith, and remedies for reputational harm. In contrast, Indonesia relies primarily on the Witness and Victim Protection Act, which offers limited and less effective protection post-disclosure. Furthermore, Malaysia’s framework clearly defines institutional responsibilities and safeguards against workplace retaliation, aspects largely missing in Indonesia. The study concludes that Indonesia should adopt key elements from Malaysia’s model to strengthen its legal framework. Enhancing whistleblower protections is essential for promoting transparency, accountability, and a more corruption-resistant governance system.